(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Elderly people have been particularly affected by the pandemic emergency. One of the most controversial issues that have characterized the public debates concerns the importance of age as a possible and controversial criterion for admission to intensive care units, due to the inability of health systems to meet the demands received within contexts characterized by the exceptional imbalance of health resources. In Italy, for example, the approval of the SIAARTI Clinical Ethics Recommendations was considered an expression of ageism, a form of structural discrimination against the elderly, which reveals the lower value assigned to their lives. In her contribution, the Author analyses the debate that has arisen in recent months, in order to understand if and within what margins this inference is justified.